Tinjauan Hukum Islam tentang Adat Istiadat Ma’rate’ dalam Acara Pernikahan (Studi Kasus Kelurahan Pantai Bahari Lambupeo’ Bangkala, Kabupaten Jeneponto) - Muhammad Taufan Djafri; Syandri, Syandri; Aswar, Aswar; Zulkarnain Alim Said (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2021)
The purpose of this study was to discover the Ma'rate customary law in marriage according to the perspective of Islamic law. This research uses a qualitative approach with the type of field research (field research) and uses a normative and socioanthropological approach. The results of the study show that Ma'rate customs are never separated from the combination of culture and Islamic law. Ma'rate in the Islamic perspective has three elements of value, namely; 1) Moral values (in Ma'rate custom the host is obliged to honor guests such as providing food); 2) Cultural values (Ma'rate custom is no longer by its implementation as in the beginning, and this change is seen from the equipment that must be provided, where Ma'rate custom is now only an effort to preserve tradition); and 3) The value of worship (in the Ma'rate custom there are activities to pray for the bride and groom and humans in general). If the community can maintain Islamic values and not fall into sin, then Islamic law shows that the Ma'rate custom can be carried out on the condition that it does not conflict with the Qur'an, the sunnah of the prophet, and the rules of ushul fiqh.